DELVING INTO THE WORLD OF NUMBERS: INNOVATIVE APPROACHES IN ELEMENTARY MATHEMATICS EDUCATION - Wahyu Purwandari; Ita Margaretta Br Tarigan, Nirwan Sinuhaji, Polin Ramles; Puji Asmaul Chusna (Adisam Publisher, 2024)
Mathematics is a subject that has a very important role in a child's future life, but in reality children are less serious, tend to find it difficult and do not like math lessons. This research aims to find out what innovative approaches are in basic mathematics education. Library data collection method, or research in which the research object is explored through various library information. The nature of this research is descriptive analysis, namely the regular analysis of the data that has been obtained, then providing understanding and explanation so that it can be understood well by the reader. The conclusion of this research is that one of the innovations in basic mathematics education is the use of interactive media, such as application-based mathematics games, animated learning videos, and interesting teaching aids. Apart from the use of technology and collaboration, other innovations include extracurricular activities and mathematics competitions to motivate children.